RELATIONSHIP PERSONAL HYGIENE AND OPPORTUNISTIC INTESTINAL PROTOZOAN INFECTIONS IN STUNTED CHILDREN IN SUKORAMBI VILLAGE - Bagus Hermansyah; Primanda Vitarani; Ayu Munawaroh Aziz; Wiwien Sugih Utami; Yunita Armiyanti; Erma Sulistyaningsih (Faculty of Vocational Studies, Universitas Airlangga, 2026)
Background: Stunting remains a major public health problem in Indonesia. Various factors contribute to chronic malnutrition, with one significant factor being infection from opportunistic intestinal protozoa. This pathogen can exacerbate chronic malnutrition by damaging the intestinal lining, which leads to inadequate nutrient absorption. Transmission of this disease occurs due to environmental sanitation and personal hygiene. Purpose: To determine the relationship between personal hygiene habits and the occurrence of opportunistic intestinal protozoan infections in stunted children in Sukorambi Village, Jember. Method: The subjects were 37 children diagnosed with stunting. Information on personal hygiene habits was collected through a questionnaire. Intestinal infections caused by opportunistic protozoa were detected using a microscope. Fisher's exact test was used to examine whether there was a significant relationship between these variables. Result: The prevalence of intestinal protozoan infections in stunted children was 18.9%. The most prevalent species was Blastocystis hominis (16.2%), followed by Cryptosporidium parvum (2.7%). No cases of Cyclospora sp. or Isospora belli were detected. A statistically significant relationship was found between personal hygiene and protozoan infection (p-value = 0.027). Conclusion: Poor personal hygiene is strongly associated with intestinal protozoan infections. Therefore, teaching caregivers, especially mothers, proper hygiene is crucial to preventing the spread of parasites among children. Furthermore, this study demonstrates the importance of health policies that focus on improving hygiene in more at-risk communities to reduce infections and stunting.